2007
DOI: 10.1371/journal.pone.0000334
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Copper Ion Mediated Huntington's Disease Progression

Abstract: Huntington's disease (HD) is caused by a dominant polyglutamine expansion within the N-terminus of huntingtin protein and results in oxidative stress, energetic insufficiency and striatal degeneration. Copper and iron are increased in the striata of HD patients, but the role of these metals in HD pathogenesis is unknown. We found, using inductively-coupled-plasma mass spectroscopy, that elevations of copper and iron found in human HD brain are reiterated in the brains of affected HD transgenic mice. Increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
165
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 171 publications
(175 citation statements)
references
References 50 publications
9
165
0
1
Order By: Relevance
“…However, excess copper also possesses toxicity (32); e.g., it has been established that brain copper accumulation is associated with neurodegeneration (33). Previous studies suggested that there might be a close relationship between copper and the progress of Huntington disease (13)(14)(15). In this study, we provided in vivo genetic evidence that manipulating copper transporters such as Ctr1B or DmATP7 in brains can greatly modulate HD progress.…”
Section: Discussionmentioning
confidence: 78%
See 4 more Smart Citations
“…However, excess copper also possesses toxicity (32); e.g., it has been established that brain copper accumulation is associated with neurodegeneration (33). Previous studies suggested that there might be a close relationship between copper and the progress of Huntington disease (13)(14)(15). In this study, we provided in vivo genetic evidence that manipulating copper transporters such as Ctr1B or DmATP7 in brains can greatly modulate HD progress.…”
Section: Discussionmentioning
confidence: 78%
“…This prompted us to investigate the interaction between Htt exon1 and copper. In line with this thinking, it has been reported that copper directly binds the first 171 amino acids of Htt (N171) in vitro (13). Both His82 and His98 residues of rodent Htt appear essential for the interaction.…”
Section: Dietary Copper Intervention Mimics the Genetic Modulation Inmentioning
confidence: 72%
See 3 more Smart Citations